Вплив товщини цементоґрунтових основ на несучу здатність бетонних дорожніх покриттів - Солодкий, С. Й.; Думич, І. Ю.; Турба, Ю. В.; Solodkyy, S.; Dumych, I.; Turba, Yu. (Видавництво Львівської політехніки, 2018)
Постійний приріст навантажень на дорожні покриття потребує постійного збільшення їх несучої здатності. Наведені результати експериментальних випробувань моделей бетонних покриттів на піскоцементних основах. Проведені експериментальні дослідження в лабораторії кафедри автомобільних доріг і мостів Національного університету “Львівська політехніка” на змодельованій ділянці покриття в масштабі 1:3 показали, що підвищувати несучу здатність бетонних дорожніх покриттів необхідно за рахунок влаштування основ із матеріалів укріплених цементом. Отримані рівняння регресії першого порядку, що характеризують залежність основних показників несучої здатності покриттів – пружних прогинів і граничних навантажень – від товщини покриттів і жорстких основ. У результаті експериментальних моделей бетонних покриттів на жорстких основах різної товщини встановлено, що по несучій здатності односантиметрова плита покриття еквівалентна приблизно 1,8–2,0 см плити жорсткої піскоцементної основи.

Permanent increasing of loading on road surfaces requires a permanent increase their bearing capacity. In research paper presented experimental results of test specimens of concrete road surfaces on cement-sand bases. The experimental tests were conduct at laboratory of department highways and bridges at Lviv Polytechnic National University. The specimens were at scale 1:3 and included six plates by sizes 2×1 m united in construction by joint type. The full-length research object was 6 m and width 2 m. Two middle plates were testing to destruction specimens. After that, in this area placed new construction of surfaces and bases. The task were to determinate comparative dependence the limit loads and deflections in different thickness of surfaces and bases for more clear and detail estimation influence of this value. For reach this tasks were used orthogonal planning of experiment in the first order for the two-factor dependence on the three levels – tested 32 = 9 constructions of surfaces. The thickness of test specimens of concrete plate were 50, 70 and 90 mm and the thickness of sand-cement bases were 0, 50 and 100 mm. The experimental results showed that for increasing bearing capacity of concrete road surfaces need to arrange bases of materials strengthened by cement. In this paper presented new results of regression equation in first order, that characterized comparative dependence the limit loads and deflections in different thickness of surfaces and rigid bases. In experimental results of concrete plate specimens on different thickness of rigid bases determinate, that bearing-capacity of 10 mm had equivalent bearing-capacity of 18–20 mm plate on rigid sand-cement bases. However, by the received experimental results, the increasing of rigid bases cannot be sharp growth and must be optimal correlation of thickness of concrete plate surfaces and bases in condition of equally tense of plates.
Influence of thickness of cement-ground bases on bearing-capacity of concrete road surfaces
Keywords: бетонні дорожні покриття; піскоцементні та цементоґрунтові основи; несуча здатність; concrete road surfaces; sand-cement bases; ground-cement bases; bearingcapacity; 625.841